Neutron emission effects on fragment mass and kinetic energy distribution from ﬁssion of Pu-239 induced by thermal neutrons - Montoya, Modesto (2010)
The average of fragment kinetic energy (<E*>) and the multiplicity of prompt neutrons (v) as a function of fragment mass (m*), as well as the fragment mass yield (Y (m*)) from thermal neutron induced ﬁssion of Pu-239, have been measured by Tsuchiya et al. In that work the mass and kinetic energy are calculated from the measured kinetic energy of one fragment and the diference of time of ﬂight of the two complementary fragments. However they do not present their results about the standard deviation σE* (m*). In this work we have made a numerical simulation of that experiment, assuming an initial distribution of the primary fragment kinetic energy (E(A)) with a constant value of the standard deviation as function of fragment mass (σE (A)). As a result of that simulation we obtain the dependence σE* (m*) which presents an enhancement between m* = 92 and m* = 110, and a peak at m* = 121.